A Powerful Turn‐On Fluorescent Probe for Phosgene: A Primary Amide Strategically Attached to an Anthracene Fluorophore. Issue 31 (16th August 2019) - Gangopadhyay, Ankita; Ali, Syed Samim; Mahapatra, Ajit Kumar
Abstract: We report here the application of a robust, selective primary amide moiety appended to a fluorescence signalling entity‐ anthracene, the sensing platform, 9‐AM with a view to fluorescent chemosensing of hazardous phosgene gas. The impressively fast (reaction time<1.5 min) detection of phosgene was achieved through the dehydration of the primary amide functionality to a nitrile group. A low detection limit of 5.56 nm ensures applicability of the probe for sensing of minute levels of phosgene well below prescribed safe limits. In addition, TLC sticks impregnated with the probe function as efficient gas phase phosgene sensors with real‐time applicability. Abstract : A highly selective and sensitive turn‐on phosgene sensor has been synthesized that utilizes fluorescence signaling via a stout blue emitting OLED precursor, anthracene for the efficient detection of poisonous phosgene gas in both liquid and gaseous media. Convenient and selective dehydration of a primary amide moiety to nitrile functionality by phosgene propels the fluorescence turn on response exhibited by the sensing platform.